Harmonized data on early stage litter decomposition using tea material across Japan. Issue 5 (5th September 2019) - Suzuki, Satoshi N.; Ataka, Mioko; Djukic, Ika; Enoki, Tsutomu; Fukuzawa, Karibu; Hirota, Mitsuru; Hishi, Takuo; Hiura, Tsutom; Hoshizaki, Kazuhiko; Ida, Hideyuki; Iguchi, Akira; Iimura, Yasuo; et al.
Abstract: Litter and soil organic matter decomposition represents one of the major drivers of carbon and nutrient cycling in a given ecosystem; however, it also contributes to a significant production of relevant greenhouse gasses. The Japanese archipelago spans several biomes (boreal‐temperate‐subtropical) and covers a large range of elevations and ecosystem types. Hence, the comprehension of this fundamental biogeochemical process in diverse ecosystems is crucial to maintain their ecosystem services. In this article, we have provided data on plant leaf decomposition from 33 research sites across Japan. At each site, standard litter material with different decomposition rates, rooibos tea and green tea were incubated for 90 days between 2012 and 2016 and the remaining mass was recorded. In total, 1904 bags were used. In addition, supplementary measurements of environmental variables essential for the interpretation of the collected data, such as soil and vegetation, were recorded. Plot‐level averages of the remaining mass rates of bag contents after incubation ranged 0.17–0.51 for green tea and 0.54–0.82 for rooibos tea. Continued monitoring will also provide important insights into the temporal dynamics of litter decomposition. Abstract : This data paper provides data on the decomposition of tea bags as a standardized plant leaf material from 87 study plots in 33 research sites across Japan. At each site, two types of tea, rooibos and green tea, were incubated for 90 days between 2012 and 2016. In total, the mass remaining rate of 1904 bags was obtained.